2014
DOI: 10.1007/s00213-014-3463-z
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual, neurocognitive, and academic achievement in abstinent adolescents with cannabis use disorder

Abstract: Rationale The active component of cannabis, delta-9 tetrahydrocannabinol (THC), has a long half-life and widespread neurocognitive effects. There are inconsistent reports of neurocognitive deficits in adults and adolescents with cannabis use disorders (CUD), particularly after a period of abstinence. Objectives To examine neurocognitive measures (IQ, academic achievement, attention, memory, executive functions) in abstinent adolescents with CUD, while controlling for demographic, psychopathology, and poly-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 58 publications
2
59
0
2
Order By: Relevance
“…Numerous studies report impairment in adolescent and adult cannabis users with a wide range of exposure as well as former users abstinent for several weeks on measures of sustained and divided attention, processing speed, rapid visual information processing, visual search, tracking, trail making, and paced serial addition (46,54,55,57,61,(91)(92)(93)(94). Users abstinent for 23 days remained impaired relative to control subjects despite improvements in sustained and divided attention with increasing abstinence (91) with poor attentional performance associated with younger age of onset in this study (91) and another study of adolescents abstinent for 30 days (95). However, no difference between abstinent former users and control subjects on broader measures of attention was also reported (57,63,64,79,95).…”
Section: Attentionmentioning
confidence: 56%
See 1 more Smart Citation
“…Numerous studies report impairment in adolescent and adult cannabis users with a wide range of exposure as well as former users abstinent for several weeks on measures of sustained and divided attention, processing speed, rapid visual information processing, visual search, tracking, trail making, and paced serial addition (46,54,55,57,61,(91)(92)(93)(94). Users abstinent for 23 days remained impaired relative to control subjects despite improvements in sustained and divided attention with increasing abstinence (91) with poor attentional performance associated with younger age of onset in this study (91) and another study of adolescents abstinent for 30 days (95). However, no difference between abstinent former users and control subjects on broader measures of attention was also reported (57,63,64,79,95).…”
Section: Attentionmentioning
confidence: 56%
“…Users abstinent for 23 days remained impaired relative to control subjects despite improvements in sustained and divided attention with increasing abstinence (91) with poor attentional performance associated with younger age of onset in this study (91) and another study of adolescents abstinent for 30 days (95). However, no difference between abstinent former users and control subjects on broader measures of attention was also reported (57,63,64,79,95). Therefore, cannabis-related attentional impairment may reflect residual effects that dissipate gradually as cannabinoids are cleared from the body (Supplement 1).…”
Section: Attentionmentioning
confidence: 61%
“…6 Amount of use of cannabinoids was also found to be a significant factor determining level of deficits. 1,8 A longitudinal study of cognitive functions from birth to adulthood, reported participants Hooper 8 with history of cannabis dependence prior to age of 18 showed neuropsychological decline over time. 9 Early use of cannabis is likely to negatively influence neurodevelopmental process occurring in adolescence.…”
Section: Determinants Of Level Of Cognitive Deficits and Recoverymentioning
confidence: 99%
“…In several cohort studies, adolescents who reported marijuana use were more likely to have impaired cognitive and academic abilities despite 28 days of abstinence [59][60][61][62].…”
Section: Adolescent Usementioning
confidence: 99%